1946
DOI: 10.1063/1.1707726
|View full text |Cite
|
Sign up to set email alerts
|

Tackiness of GR-S and Other Elastomers

Abstract: The deficiency of GR-S in ``tackiness'' resulted in a great deal of work in the rubber industry to improve this complex property, but practically all the work had to be evaluated by qualitative ``hand tests'' because quantitative tests were not available. An analysis of the factors involved in the ``tackiness'' of various materials showed that different factors were critical in the so-called ``tackiness'' of rubber, paints, and varnishes, printing inks, adhesive tapes, etc. A quantitative test was developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1946
1946
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…In literature, it has also been shown that addition of reinforcing fillers such as carbon black can substantially increase the tack strength of elastomers [11][12][13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In literature, it has also been shown that addition of reinforcing fillers such as carbon black can substantially increase the tack strength of elastomers [11][12][13].…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, addition of carbon black to styrene butadiene rubber (SBR) resulted in a significant reduction in the tack strength [1]. It was already established by Busse et al that SBR used in their study could not readily achieve bond formation due to the unfavorable intrinsic characteristics of the elastomer such as molecular weight and viscosity [12]. The addition of filler further restricts the chain mobility, reducing the interfacial interactions leading to lower tack.…”
Section: Introductionmentioning
confidence: 99%
“…The peel test is a simple and commonly used method to quantify bulk adhesion between two surfaces . A fracture mechanics interpretation of the adhesive's detachment is used to obtain and compare the adhesive strength and energy of specimens tested in different peel configurations .…”
Section: Introductionmentioning
confidence: 99%
“…It is an important property of contact adhesives as well as for rubbery compositions used in the manufacture of multilayer composites such as tires. [1][2][3][4][5] When a conventional adhesive joint is formed, the adhesive is fluid to hasten wetting, and then sets by chemical or physical action to strengthen. However, in 96 G. R. HAMED AND G. D. ROBERTS autohesion the material remains in the same state during, and subsequent to, bond formation.…”
Section: Introductionmentioning
confidence: 99%